RELASI KONSEPTUAL ILMU NEGARA DAN PENGANTAR ILMU HUKUM DALAM SISTEM PENDIDIKAN HUKUM INDONESIA - A., AZIZ PANJI (Fakultas Hukum Universitas Narotama, 2026)
This study examines the conceptual relationship between State Science (Staatslehre) and Introduction to Legal Studies (PIH) as two foundational courses in Indonesian legal education. The central problem addressed is why two disciplines that conceptually support each other are consistently treated as independent entities in the curriculum, and what the intellectual consequences of this separation are. This study employs normative legal research methodology using conceptual and comparative approaches. Primary legal materials include statutory provisions relevant to the formation of Indonesia's rechtsstaat, while secondary legal materialsencompass literature in constitutional law theory, state theory, and legal philosophy from verifiable sources. The findings demonstrate that State Science and PIH stand in a coconstitutive relationship: State Science provides the ontological foundation for why the state has authority to create and enforce law, while PIH explains how that authority is actualized within a positive norm system. The concept of the rechtsstaat constitutes the strongest intersection point between them. The existing pedagogical separation produces a structural comprehension deficit in law students, and this study argues that curricular integration is not merely a pedagogical preference but a requirement of epistemological coherence. Keywords: State Science, Introduction to Legal Studies, Staatslehre, Rechtsstaat, Normative Legal Education